Salivary vitamin E and uric acid in patients with OLP and healthy individuals - Adel J Mohammed; Ameena R Diajil (College of Dentistry/ University of Baghdad, 2019)
Background: Oral Lichen planus (OLP) is a T-cell mediated chronic inflammatory oral mucosal disease of unknown etiology. Recent studies have reported an increased oxidative stress and lipid peroxidation in such patients. This suggests that reactive oxygen species may have a role in the pathogenesis of lichen planus. Oxidative stress in OLP release molecules consisting of granzymes resulting in local tissue damage in the effectors. Antioxidants that can defend against oxidative stress in the body cells include enzymes, as well as non- enzymatic antioxidants, such as melatonin, uric acid, vitamin A and E. Purpose: To study the level of salivary vitamin E and uric acid as antioxidant agents in patients with OLP and compared with healthy control. Methods: Twenty five patients with OLP were enrolled in this study. Age, gender, occupation, smoking status (smokers or non-smokers), lesion types, duration, location and size were recorded for each patient. After an oral examination, salivary samples were collected and flow rates (ml/min) were recorded. The collected samples were centrifuged at 3000 rpm for 10 minutes; the clear supernatants were separated and stored frozen at (-20 c) until analysis. Then salivary vitamin E was investigated using ELISA kit based on bioten double antibody sandwich technology. Uric acid was analyzed using a proprietary enzymatic reaction mixture that enables the detection of uric acid by the production of a red chromogen, which is quantitatively measured at a wavelength of 515 or 520 nm. Results: The mean age of OLP patients was 48.3 years with a range of 30-60 years. Control group consisted of 35 healthy subjects who were age matched with OLP patients. Fourteen (56%) patients were with reticular and 11 (44%) were with erosive form, with the buccal mucosa was the most commonly affected site (88%), followed by tongue (8%) then gingiva (4%). A significantly lower salivary flow-rate, lower salivary vitamin E and uric acid level in OLP patients compared to control; while, no significant difference was seen between reticular and erosive type of OLP for both vitamin E and uric acid level. Regarding gender, no differences were found between males and females in salivary vitamin E. No significant correlation was found between vitamin E /uric acid and age. Similarly, no difference was found between males and females in uric acid. Conclusion: Salivary anti-oxidant markers represented by vitamin E and uric acid decreased in OLP patients due to increase oxidative stress which may have an important role in the pathogenesis. Thus, it is recommended to give OLP patients anti-oxidant agents that may either help in healing process or decreased the severity.